DESAIN MOZAIK PADA INTERIOR PERSEGI BERKARAKTER BARISAN GEOMETRI - Murihani, Endang; Kusno, K; Susanto, Kiswara Agung (Kadikma, 2012)
Abstract. Mosaic is a creation that arrangs a piece of geometric in a space. This mosaic design which has geometric line character enrichs the-varieties of mosaic designs more attractive and various. The result of research is to develop the mosaic design in rectangle interior for geometric line the character and it needs some steps follows: (1) constructing pieces of rectangle in which the size is arranged in geometric line form through spot among each side, (2) fill each piece with the previous result step (1) fill curve permanently or exchang by using the rotation or dilatation, (3) combains some rectangles with the previous result (2) and colors the background or the filling curve.   Key Words: geometric line, mosaic design.